Anomalous Thermal Expansion and Luminescence Thermochromism in Silver(I) Dicyanamide. Issue 27 (10th June 2016) - Hodgson, Sarah A.; Hunt, Sarah J.; Sørensen, Thomas Just; Thompson, Amber L.; Reynolds, Emily M.; Faulkner, Stephen; Goodwin, Andrew L.
Abstract : We study mechanical flexibility and its link to optical properties in the dense metal–organic framework silver(I) dicyanamide {Ag[N(CN)2 ], Ag(dca)}. We show that the system exhibits polymorph‐independent anomalous thermal expansion behaviour and find a linear variation in the relative intensity of emission bands with temperature, indicative of thermochromism in the Ag‐centered luminescence. Abstract : Silver(I) dicyanamide exhibits both mechanical and optical sensitivity to temperature. This responsive metal–organic framework may find application in high‐precision temperature sensors.